Folke - Språkbanken Text (University of Gothenburg, 2025)
Folke is a digital archive service developed by Isof and Språkbanken. In
Folke, there are hundreds of thousands of scanned historical folklore
records from Isof's collections, and by the end of 2024, more than
30,000 pages had been transcribed through citizen science. The material
was primarily collected during the first half of the 20th century and
highlights people's lives and work, daily routines and celebrations,
experiences, and memories, from the late 19th century onwards.
The transcribed texts in Folke are now available in Korp. The corpus is
continuously updated as the transcription of material in Folke
progresses.
Link to Folke: https://sok.folke.isof.se/
Read more about Folke on Isof's website:
https://www.isof.se/folkminnen/folke

Folke är en digital arkivtjänst som utvecklas av Isof och Språkbanken. I
Folke finns hundratusentals inskannade äldre folkminnesuppteckningar
från Isofs samlingar, och vid slutet av årsskiftet 2024 var mer än 30
000 sidor transkriberade via medborgarforskning. Materialet är framför
allt insamlat under första hälften av 1900-talet och belyser människors
liv och arbete, vardag och fest, erfarenheter och minnen, från slutet
av 1800-talet och framåt.
De transkriberade texterna i Folke finns nu tillgängliga i Korp.
Korpusen uppdateras kontinuerligt i takt med att transkriberingen av
material på Folke fortskrider.
Länk till Folke: https://sok.folke.isof.se/
Läs mer om Folke på Isofs webbplats:
https://www.isof.se/folkminnen/folke
Folke
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik